BOOK SELECTION BASED ON CHILDREN'S BOOK COVERS: ANALYSIS MULTIMODALITY - Dina Oktafiani; Retno Purwani Sari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This study discusses the results of investigations into book selection research based on covers in children aged 3-12 years. The aim is to find out how verbal and visual modes are represented in children's book covers and identify whether they influence children's decisions to buy books. This research focuses on the identification of multimodality texts and visual modes in children's books "Words of Life" and "A Dash of Magic." The Multimodal Discourse Analysis Theory (MDA) by Kress and van Lueeween is applied by systematically describing the data found on the covers of children's books. Based on the analysis, it was found that there were three metafunctions found; representational, interactive, and compositional; each plays a certain role in the cover of this child's book. Moreover, research also shows that children aged 3-12 years buy books because they are interested in book covers, with 83.3% of children agreeing to buy books that have engaging titles, images, colors, and designs.